Analisis Karakteristik Item Ujian Nasional IPA SMP Berdasarkan Pendekatan Teori Tes Klasik - Mariana Mariana; Djaffar Lessy; Dinar Riaddin; Muhammad Rizal Hardiansyah; Corneli Pary (Postgraduate, University of Mataram, 2023)
This study aims to analyze the characteristics of the items based on the classical test theory approach. This research is exploratory research with a quantitative approach. The data used in this study were data from the 2015 Science Subject National Examination for Junior High School in Daerah Istimewa Yogyakarta (DIY) province. The samples taken in this study were 9054 students. Test takers are grouped into high groups and low groups based on the total score obtained. Estimation of item parameters using Excel and QUEST. The results of the analysis show that based on the classical test theory approach, the average item difficulty level ) in the high group is in the easy category, while in the low group, it is in the medium category, the average item differential index ( ) shows that the test ability to distinguish students with high abilities and low abilities in both the high and low groups is in the unfavorable category; and the reliability coefficient of the test (Ï) in the high group has high reliability, and the low group has perfect reliability